The Ecosystem of openKONSEQUENZ, a User-Led Open Source Foundation - Schwab, Bettina; Riehle, Dirk; Barcomb, Ann; Harutyunyan, Nikolay (Proceedings of the 16th International Conference on Open Source Systems 2020 (OSS 2020), 2020)
Companies without expertise in software development can opt to form consortia to develop open source software to meet their needs, as an alternative to the build-or-buy decision. Such user-led foundations are little understood, due to a limited number of published examples. In particular, almost nothing is known about the ecosystems surrounding user-led foundations. Our work seeks to address this gap, through an exploratory qualitative survey of openKONSEQUENZ, from the German energy sector. We find that the technological goals are quite homogeneous, independent of a participant’s role in the ecosystem, but that economic conflicts exist between foundation members and supplier companies due to the consortium’s efforts to transform the software market structure to limit dependency on specific vendor
Keywords: open source foundations; sponsored open source; commercial open source; open source software; user-led open source foundations